Efisiensi Pemasaran Cabai Rawit Merah di Desa Cidatar Kecamatan Cisurupan Kabupaten Garut - Adrianus Hia; Rita Nurmalina; Amzul Rifin (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2020)
The research marketing efficiency of red cayenne pepper was located in the Cidatar part of Cisurupan regency Garut district purposed to know marketing channel, marketing margin, and farmer’s share. The research used descriptive analysis method. About 31 farmers were chosen with a random sampling method and with the snowball method to got 10 sellers. Interview and observation in collecting primary data while the documentation to retrieve secondary data. There are five red cayenne pepper marketing channels in Cidatar, Cisurupan District, Garut Regency. The marketing channels are, I) farmer – a collector – wholesaler Jakarta – retailer – consumer Jakarta; II) farmer – a collector – wholesaler Cikajang– retailer – consumer Cikajang; III) farmer – a collector – wholesaler Cikajang – wholesaler Jakarta – retailer – consumer Jakarta; IV) farmer – a collector – wholesaler Bandung – retailer – consumer Bandung; V) farmer – a collector – wholesaler Bandung – wholesaler Jakarta – retailer – consumer Jakarta. The margin analysis results that the smallest marketing margin is in marketing channel II at 52,3 per cent. The largest Farmer’s share is at 47 per cent in marketing channel II and the biggest ratio of πi/Ci is at 5,64 in marketing channel III. The suggestion that can be given to farmers is to choose marketing channel I because channel I am the channel with the great packing volume that may be delivered by the market and also the highest price compared to other marketing channels.